Anti-T (Thomsen-Friedenreich) agglutinin in chagas' disease - Palatnik, Marcos (1986)
Serum samples of patients with Chagas'disease and controls from an endemic area of this country were titrated against neuraminidase treated blood group 0 (0T-activated cells) and normal A and B (ABO) red cells. In addition, some agglutination tests with peanut (anti-T + anti Tk), soybean (anti-T) lectins and human anti-T antibody were performed on red cells from cardiomyopathy patients. The average anti-T score of patients was similar to that of the control group. However, the average score of individuals with the cardiac form was significantly higher than that of assymptomatic patients, and also higher than that of the control sera. The comparison between individuals with positive versus negative serology for Chagas'disease was not significant. Neither diagnostic serology nor the variables race, sex, age, age squared, intestinal parasitic infection, serum protein level, packed red cell volume, degree of bucal mucous membrane paleness, cardiomyopathy and the interaction terms sex x age, sex x age squared, were significantly associated with log titre or log score. The ABO agglutinin scores fell within the normal range of variation. Neither T and Tk receptors nor immunoglobulins (Direct Coombs'test could be detected on the red cell membrane of patients with the cardiac form. The fact that the increase of anti-T levels has been detected only in one of the forms of the disease in patients of the same endemic area strongly argues against the possibility of a concomitant infection as the cause of the observed variations.